Models and Challenges in Implementing Individual and Group Guidance Services in Primary Schools: A Systematic Literature Review - Safitri Masdaliatul Luluk Iyah; Rabawati Rabawati (EDOVA JOURNAL : Education for Nation Development Journal, 2025)
This study aims to analyze the implementation of individual and group guidance services in primary schools, as well as to identify the challenges and potential directions for their development. Individual guidance services focus on helping students address personal problems, enhance self-confidence, and improve learning motivation, whereas group guidance services aim to develop students’ social skills and cooperation. The method employed was a literature review using a qualitative descriptive approach, with data collected from journal articles, books, and research reports and analyzed through content analysis techniques. The findings indicate that individual guidance is effective in assisting students in overcoming personal issues, while group guidance has a positive impact on social skills development. However, several challenges were identified, including limited training for classroom teachers, insufficient time allocated for guidance activities, and a lack of policies supporting the integration of guidance services into the primary education curriculum. From a theoretical perspective, gaps remain in integrating child development theories, such as those proposed by Piaget and Erikson, with holistic guidance practices. This study recommends the development of a more structured guidance service model that actively involves classroom teachers as key facilitators, supported by intensive training. Further research is needed to examine the effectiveness of this model across diverse contexts, including urban and rural settings.